2005
DOI: 10.1038/sj.ejcn.1602224
|View full text |Cite
|
Sign up to set email alerts
|

A low-protein diet exacerbates postprandial chylomicron concentration in moderately dyslipidaemic subjects in comparison to a lean red meat protein-enriched diet

Abstract: Objective: To investigate whether altering energy intake as red meat protein or carbohydrate modifies chylomicron homeostasis and postprandial lipaemia. Design: Randomized single-blind dietary intervention trial. Setting: School of Public Health, Division of Health Science, Curtin University, Perth, Western Australia. Subjects: A total of 20 moderately hypertriglyceridaemic but otherwise healthy subjects were recruited and completed the study. Intervention: Participants consumed an isocaloric weight maintenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…Following a fat challenge, participants on the high-protein diet had an attenuated increase in ApoB-48 concentration (∌85% less than the increase in subjects on the low-protein diet). There was no difference in insulin sensitivity or weight between the groups (90). Notably, the low-protein group had a higher carbohydrate intake, and therefore whether the effect on chylomicron concentration was causally linked to differing protein intake alone is not known.…”
Section: Proteinmentioning
confidence: 72%
See 1 more Smart Citation
“…Following a fat challenge, participants on the high-protein diet had an attenuated increase in ApoB-48 concentration (∌85% less than the increase in subjects on the low-protein diet). There was no difference in insulin sensitivity or weight between the groups (90). Notably, the low-protein group had a higher carbohydrate intake, and therefore whether the effect on chylomicron concentration was causally linked to differing protein intake alone is not known.…”
Section: Proteinmentioning
confidence: 72%
“…Mamo et al (90) compared the effects of six weeks' consumption of two isocaloric diets in mildly hypertriglyceridemic men; one diet was high in protein in the form of lean red meat, and the other had lower protein content. Following a fat challenge, participants on the high-protein diet had an attenuated increase in ApoB-48 concentration (∌85% less than the increase in subjects on the low-protein diet).…”
Section: Proteinmentioning
confidence: 99%
“…Information about the influence of dietary protein on postprandial lipemia is, however, scarce. In nondiabetic subjects, it has been shown that casein reduces postprandial lipemia to a fatty meal (19) and that daily moderate consumption of a protein-enriched diet with lean red meat attenuates postprandial chylomicronemia (20). However, no information exists on the effect of protein on postprandial lipemia in type 2 diabetes.…”
Section: Introductionmentioning
confidence: 92%
“…134 Similarly, hypertriglyceridemic individuals who consume a low protein diet appear to develop an exaggerated postprandial chylomicron response, as indicated by increased postprandial ApoB48. 135 Exercise and concomitant weight loss also have an important role in the management of postprandial dysmetabolism. The American Diabetes Association Guidelines recommend a target of 7% weight loss and increase of their moderate-intensity physical activity to at least 150 min/week.…”
Section: Dietary Modification and Exercisementioning
confidence: 99%